Given the system of equations { x ( x + y ) y ( x + y ) = = 9 1 6 the value of x y can be written as b a where a and b are positive coprime integers. Find a + b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
For those who didn't get the third line -
x ( x + y ) + y ( x + y ) = 2 5
Here , we simply common out ( x + y ) to get -
( x + y ) ⋅ ( x + y ) = 5 2
Tried my best to make it understandable , elegant and short .
( x + y ) can be 5 or -5.
Log in to reply
True , I completely forgot to include that point too.
Putting : ( x + y ) 2 = 5 2
Will not change the solution.
BTW , the value of :
( x + y ) = ± 5
Log in to reply
yes it won't change the solution but both the equations are satisfied when x and y are of the same sign i.e either positive or negative
In fact, there isn't a need to even say that ( x + y ) = ± 5 . I have removed that distracting detail from your solution, which makes it much better.
This was the approach that I used to solve (and create) this problem.
Log in to reply
@Calvin Lin – Thank you very much for helping me sir . I intended to do the same ( If I had the opportunity)
Thanks a lot.
Awesome dude! Exactly the way I did it! I mean ... EXACTLY!
xy(x+y)^2 = 9*16/25
Adding the equations after distribution,
x 2 + x y = 9 plus
+ x y + y 2 = 1 6 equals
x 2 + 2 x y + y 2 = 2 5
Recognizing the perfect squares,
( x + y ) 2 = 5 2 .
Taking square roots,
x + y = 5 .
Substituting,
x ( 5 ) = 9 and y ( 5 ) = 1 6 .
Solving for variables,
x = 5 9 and y = 5 1 6 .
Multiplying for the answer x y ,
2 5 1 4 4 means a + b = 1 6 9 .
Why must we have x + y = 5 ?
Log in to reply
I think I see now, Calvin.
It is false to say that x + y = 5 , but it is possible to prove that ( x + y ) 2 = 2 5 . More specifically, x + y has two values and so a statement assuming only one of these values would be incorrect. That means my solution was a bit incorrect and I see the value of Priyansh's solution in that he just avoided the whole mess. In answer to your question, "We mustn't." If I really wanted to continue the method I used, I should make two cases for x + y = 5 and x + y = − 5 , solve each, then show they are equivalent. But that is more work.
Silly me... Thanks for helping me be a better mathematician. I appreciate how you always address flaws in solutions.
Log in to reply
This question was designed to catch such a mistake, namely making a claim that x 2 = 1 ⇒ x = 1 . Of course, when stated this way, it seems obvious to everyone. I just disguised it in the form ( x + y ) 2 = 2 5 ⇒ ( x + y ) = 5 .
Good identification of the error and reflecting on how to resolve the issue. Keep u the good work, and I'm sure you'd soar.
I know that you're right but I don't understand how you get rid of the 2xy in the third step to give the (x+y)^2 = 25?
Log in to reply
Because ( x + y ) 2 = x 2 + 2xy + y 2
X(X+Y)=9.....EQN.1 Y(X+y)=16....EQN.2 Dividing 1 by 2. We get:X=9Y Now substracting 1 and 2 we get: X(X+Y)-Y (X+Y)=-7 Y.Y-X.X =7 By Substituting: we get: Y=16/5 and X=9/5 Then XY=144/25 X+Y=144+25=169
If we let
x ( x + y ) = 9 be (eq 1)
and
y ( x + y ) = 16 be (eq 2)
then (1) + (2):
x ( x + y ) + y ( x + y ) = 9 + 16 = 25
by factoring:
( x + y ) × ( x + y ) = 5 × 5
or
( x + y ) 2 = 5 2
taking the square root of both sides, we will get
x + y = 5 (eq 3) or x + y = -5 (eq 4)
Substitute (eq 3) and (eq 4) to (eq 1) and (eq 2) and simlifying, we can get
x = 5 9 or 5 − 9
y = 5 1 6 or 5 − 1 6
Therefore
xy = 5 9 × 5 1 6 or 5 − 9 × 5 − 1 6
which both yields
xy = 2 5 1 4 4
Therefore, a = 144 and b = 25 and a + b = 169
x 2 + x y = 9
y 2 + x y = 1 6
Adding the two equations give us this:
x 2 + 2 x y + y 2 = 2 5
( x + y ) 2 = 2 5
x + y = 5
Substituting into the original, we get:
5 x = 9
x = 5 9
5 y = 1 6
y = 5 1 6
Multiplying it together, we get 5 1 6 × 5 9 = 2 5 1 4 4
1 4 4 + 2 5 = 1 6 9
Why must we have x + y = 5 ?
Log in to reply
I forgot to do something. ( x + y ) 2 = 2 5 , so x + y = ± 5 . It will give you the same answer regardless.
we note that x+y=a
so ax=9 and ay=19
ax+ay=25 then we can simplified them to a^2=25.
we multiply the first term and second term which we will got xya^2=144
OK now is the last step to find the answer by replace a^2 with 25
so a+b =169
sum all of the equation and you'll get x^2+2xy+y^2=25
(x+y)^2=25 >>> x+y=5
therefore 5x=9 >>>x=9/5
5y=16 >>>> y=16/5
xy=9/5*16/5=144/25=a/b
a+b= 144+25=169
On adding both equations, we get -
x 2 + 2 x y + y 2 = 2 5 ⇒ x + y = 5
On subtracting e q n ( i i ) from e q n ( i ) , we get-
y 2 − x 2 = 7 ⇒ ( y + x ) ( y − x ) = 7 ⇒ y − x = 5 7
This gives x = 5 9 and y = 5 1 6 . Hence x y = 2 5 1 4 4 = b a
Therefore, a + b = 1 6 9
Dividing the two equations, we get $$\frac{x}{y}=\frac{9}{16} \Rightarrow \frac{y}{x}=\frac{16}{9}.$$ Expanding the equations and adding, we get $$x^2+y^2+2xy=25.$$ Because x 2 + y 2 can be expressed as x y ( y x + y x ) , we can rewrite our summed equation as $$xy(\frac{x}{y}+\frac{x}{y})+2xy=25.$$ But x y ( y x + y x ) = x y ( 1 6 9 + 9 1 6 ) = 1 4 4 3 3 7 x y . Now our summed equation becomes $$\frac{337xy}{144}+2xy=25 \Rightarrow \frac{625xy}{144}=25 \Rightarrow xy=\frac{144}{25}=\frac{a}{b}.$$ Therefore, a + b = 1 4 4 + 2 5 = 1 6 9 .
I meant to put $$xy(\frac{x}{y}+\frac{y}{x})$$ instead of $$xy(\frac{x}{y}+\frac{x}{y})$$.
x(x+y)=9 ......eqn 1
y(x+y)=16 ......eqn 2
eqn 1 + eqn 2
we get:
x^2 + 2 x*y + y^2 = 9+16
(x+y)^2=25
(x + y)=sqrt(25)
x+y=5 .....eqn 3
sub eqn 3 in eqn 1
we get:
x(5)=9
x=9/5
sub eqn 3 in eqn 2
we get:
y(5)=16
y=16/5
to find: x*y
x y=(9/5) (16/5)
x*y=144/25 ......eqn 4
given that x*y=a/b .....eqn 5
comparing eqn 4 and eqn 5
we get: a=144 , b=25
(a+b)=144+25
(a+b)=169
ANS 169
Use Latex please...it's hard to understand without proper formatting
From the first equation we get ( x + y ) = x 9 putting this in second equation we get y = 9 1 6 x putting this again in the second equation x = + − 5 9 and y = + − 5 1 6 .As x and y should be of the same sign to satisfy the equations x y = 2 5 1 4 4
Simple substitutions can be more shorter than finding values. I hope you get my point.
x(x+y) = 9 y(x+y) = 16
x^2 + xy = 9 y^2 + xy = 16
adding the two eq.
(x+y)^2 = 25 x + y = 5
substituting to the first eqs.
x(5) = 9 x = 9/5
y(5) = 16 y = 16/5
Hence, xy = (16/5)(9/5) = 144/25
therefore a+b = 169
Try to answer using LATEX . It will make your solution readable .
Problem Loading...
Note Loading...
Set Loading...
Okay.
First we add the two equations to find out ( x + y ) .
x ( x + y ) + y ( x + y ) = 2 5
⇒ ( x + y ) 2 = 5 2
Now to get x y we multiply the two equations :
x y ⋅ ( x + y ) 2 = 9 ⋅ 1 6
⇒ x y = 2 5 1 4 4
Which is of the form b a
Now since , a and b are coprime ,
a + b = 1 4 4 + 2 5 = 1 6 9
Therefore , 1 6 9 is the correct answer .
Cheers!